2015
DOI: 10.1016/j.neuron.2015.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Contributions to Short-Term Memory for Orienting Movements

Abstract: Neural activity in frontal cortical areas has been causally linked to short-term memory (STM), but whether this activity is necessary for forming, maintaining, or reading out STM remains unclear. In rats performing a memory-guided orienting task, the frontal orienting fields in cortex (FOF) are considered critical for STM maintenance, and during each trial, display a monotonically increasing neural encoding for STM. Here, we transiently inactivated either the FOF or the superior colliculus, and found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 49 publications
(97 reference statements)
15
133
2
1
Order By: Relevance
“…To causally test the role of delay period activity in WM, recent work has focused on single-trial analyses of neural activity and behavior and on the impact of optogenetic perturbations on the behavioral reports at the end of the delay period; as argued by Panzeri et al (2017), these two techniques provide powerful tests of the causal role of neural activities in driving behavior. This work shows that, even over trials in which the animal had to remember the same presented stimulus, differences in the delay period activities are predictive of subsequent differences in the behavior (Kopec et al 2015, Li et al 2016, Vergara et al 2016, Wimmer et al 2014). Moreover, optogenetic perturbations to the neural activities during the delay period cause predictable changes in the subsequent behavior (Kopec et al 2015, Li et al 2016, Liu et al 2014).…”
Section: Overviewmentioning
confidence: 73%
See 1 more Smart Citation
“…To causally test the role of delay period activity in WM, recent work has focused on single-trial analyses of neural activity and behavior and on the impact of optogenetic perturbations on the behavioral reports at the end of the delay period; as argued by Panzeri et al (2017), these two techniques provide powerful tests of the causal role of neural activities in driving behavior. This work shows that, even over trials in which the animal had to remember the same presented stimulus, differences in the delay period activities are predictive of subsequent differences in the behavior (Kopec et al 2015, Li et al 2016, Vergara et al 2016, Wimmer et al 2014). Moreover, optogenetic perturbations to the neural activities during the delay period cause predictable changes in the subsequent behavior (Kopec et al 2015, Li et al 2016, Liu et al 2014).…”
Section: Overviewmentioning
confidence: 73%
“…Recent work has expanded to rodents, in which genetic tools allow neural activities to be manipulated as well as recorded. That work has focused on rodent homologs of the primate brain areas involved in memory and movement planning, including the parietal cortex, PFC, anterior lateral motor cortex (ALM), frontal orienting fields (FOF), and superior colliculus (SC) (Harvey et al 2012, Kopec et al 2015, Li et al 2016, Liu et al 2014). In rodents, elevated delay period firing is observed as in the monkey, but relatively few cells are active for the entire delay period.…”
Section: Overviewmentioning
confidence: 99%
“…After ipsilateral photoinhibition ALM activity rapidly recovered to the unperturbed trajectory (Figs 1, 3). This is inconsistent with attractors with a pair of fixed points (one for each choice condition) 29 . Upon release from perturbation these models decay to the final fixed point and do not return to the trajectory (Extended Data Fig.…”
Section: Robust Model Networkmentioning
confidence: 99%
“…Lesions of M2 in rats cause a deficit in orienting, while microstimulation elicits orienting type behaviors (Cowey & Bozek, 1974; Sinnamon & Galer, 1984). A recent study has indicated that both the M2 and the SCl are involved in the generation of short term memory representations that are required for sensory orienting (Kopec, Erlich, Brunton, Deisseroth, & Brody, 2015). Taken together this information lends weight to the role of the M2 area in guiding orienting approach related behaviors which are mediated via the SCl.…”
Section: Discussionmentioning
confidence: 99%